Familiarizing Livestock Advisory Services to Reduce Cattle Raiding in South Sudan - Ajak, J.D.A.; Demiryurek, K. (EScience Press, 2021)
In South Sudan, cattle raiding is an enduring practice among many communities and leads by cultural norms and customs. The issue has become challenging to the development of the livestock sector in the country. For the last 5-6 years 2015 to 2020, thousands of cattle heads were stolen from the cattle camps, many lives were lost during the raid, and many developmental projects were immobile. Extension in reducing cattle raiding has been seen as significant by the government, community chiefs of the rural areas, youth leaders, women, and NGOs working in the livestock sector. The improvement of the extension's role is an essential factor for reducing cattle raids among South Sudan communities. The extension can bring development opportunities, facilities, and empowerment. Accordingly, by reviewing the literature, this paper fact out which asset is necessary to reduce cattle raids. Also, the paper examines how an extension could mitigate cattle raiding through mediation. The recompenses of extension as the solution for competing cattle raids have been emphasized. The paper recommends that advisory service should have extensive training program on. on social change, building resilience through communityenhancing livelihoods, and shifting their mindsets from cattle raiding to accumulate wealth to ensure productive asset creation. The Advisory services should work as alarming tools for any expected raiding casualties in their working area. © The Author(s) 2021.
Keywords: Advisory Services; Cattle Raiding; Conflict; Extension; NGOs